(3GdJQHjI GdUMjI h GdCeGfs - (3QTGO fGOjI eMeOs ((3GdGScfOQjIs (3efTGI GdeYGQas, 2000)
(3jJWQb dOQGSI HYV GdeTcdGJ GdUMjI GdeJhGQKI h GdMOjKI Ydi eLJeYfG, eKd cjajI GdeMGaXI Ydi GdUMI, JZPjI GdQjGVj, GdOhQI GdTgQjI h GdJZjQGJ GdeUGMHI dgG, h fGbT eTcdI GdJONjf h CKGQgG Ydi GdUMI, ceG JWQb deQV GdSQWGf cOGA GdYUQ, bOe WQjbI GdhbGjI ef EUGHGJ GdedGYH(B.s
Keywords: (3GdGOeGfs; (3GdUMI GdYGeIs